103k views
0 votes
How to solve this question

How to solve this question-example-1
User Rocco
by
5.6k points

1 Answer

2 votes
To solve these series of equations, you would substitute each given value into where "y" is located in the equation. After simplifying/solving each equation, you will see what each "y "gives you.

Our equation: f(y)=5y-3

6) f(7)= 5(7)-3
f(7)= 35-3
f(y)= 32

7) f(-1)= 5(-1)-3
f(-1)= -5-3
f(-1)= -8

8) f(-3)= 5(-3)-3
f(-3)= -15-3
f(-3)= -18

9) f(6)= 5(6)-3
f(6)= 30-3
f(6)= 27

10) f(-8)= 5(-8)-3
f(-8)= -40-3
f(-8)= -43

User Polster
by
6.0k points